(untitled) - Chang, Raymond (Boston, 2007)
This supplement contains detailed solutions and explanations for all even-numbered problems in the main text. The manual also includes a detailed discussion of different types of problems and approaches to solving chemical problems and tutorial solutions for many of the end-of-chapter problems in the text, along with strategies for solving them.
Keywords: Chemistry,Hóa học